PENINGKATAN PERILAKU PROSOSIAL DALAM SEKOLAH DASAR - Haura Zain Abidah (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2024)
In human society, individuals must interact with others because humans are inherently social beings. Being part of a community or socializing requires a mutual attitude of love and respect, including helping one another. This prosocial behavior forms a continuous chain of civilization. The true essence of prosocial behavior has been defined by many psychologists. Simply put, prosocial behavior is any action intended to benefit others. Prosocial behavior emerges from social interactions and is characterized by actions or plans designed to assist others, regardless of the helper's motives.